(untitled) (Orinoquia, 2023)
The environmental impact generated by the aquaculture industry is related to water contamination resulting from the excretion of cultivated organisms, uneaten food, feces, nutrients, organic and inorganic compounds, and conditions directly related to the type of culture, traditionally land pond systems. On the other hand, the industry faces difficulties related to the need for high-quality food. The biofloc culture system (BFT) is considered a sustainable and environmentally friendly alternative because it requires a minimum exchange of water, and nutrients are recycled by the microorganisms that live there. This system generates a high accumulation of microbial biomass that must be removed. It has been the subject of research as an alternative ingredient in industry because of its considerable proportions of crude protein and lipids have been demonstrated. Biofloc meal has been proposed as an alternative protein source to replace traditional fishmeal, oil, and soybean meal, among others. This review provides information on the current knowledge of nutritional components, methods of obtaining them, their inclusion in the diet of aquatic organisms, their application in the circular economy, and their use in the diets of native species.